DCCP video streaming over multiple connections in the wireless internet. (1st January 2011) - Saleh Al-Majeed, Salah M.; Fleury, Martin
Multiplexing a single video stream over several datagram congestion control (DCCP) connections is a way of coping with wireless channel losses and traffic congestion in the wireless internet, without the need for complex cross-layer intervention. Multi-connections introduce the need for data re-ordering at the receiver. This paper considers the potential delay at an uplink destination on the internet and extends this to a scheme for user-to-user mobile device communication via the wired internet. It also considers the impact on video quality of packet drops due both to channel loss and router buffer overflow, when the DCCP congestion controller is applied. Results for IEEE 802.16e (mobile WiMAX) broadband wireless stages show a worthwhile gain in video quality from using three or more connections over a single connection but with start-up delay due to the need to avoid possible buffer underflow. More connections will be necessary to preserve sufficient wireless link utilisation if the path is lengthened to reach an end device that is also mobile.